Christian Leadership In The Midst Of Secular Life - Debora Sitohang; Ketler Sitohang; Ovawati Habayaha; Binsar Simanjuntak; Ivan Siburian; Devi Nopita Sere Nadeak (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
A Christian leader is someone whom God has called as a leader. Christian leaders should be people who are called by God and have qualifications that continue to grow in personality and Christ-like character. Christian leadership is a form of leadership that is based on Christian values and teachings, such as love, humility, service, integrity, and justice. In this context, Christian leadership not only aims to achieve organizational or community goals, but also to bring positive impact in the lives of individuals and society through a compassionate and ethical approach. The success of a leadership is due to the cooperation between the leading and the led generations. As a leader, one must know which principles to follow and uphold them in their leadership. A Christian leader should embrace the leadership principles of the successful leaders recorded in the Bible. Here are the principles of Christian leadership today. Secular comes from the Latin word saeculum, which means space and time. Space refers to the worldly sense, while time refers to the present age. Secular life principles are views or values that are not associated with a particular religion or religious belief. These principles often include concepts such as freedom of thought, tolerance, equality and the separation of religion from public affairs. Secular life emphasizes the importance of rationality, science, and individual freedom of decision without religious interference. Secularism is broadly speaking an ideology that states that a state institution or body should stand apart from religion or belief. Secularism also refers to the notion that human activities and determinations, especially political ones, should be based on what is considered to be concrete evidence and facts, and not on religious influences. In political terms, secularism is the movement towards the separation of religion and government, one example being the replacement of religious law with civil law. This is said to promote democracy by protecting the rights of religious minorities.